DESIGN OF METHOD FOR THE CONSTRUCTION OF THE GEDEBAGE MUSIC CONCERT HALL - HARDIANTO (NIM: 15014037), LAURENSIUS
Music Concert Hall in Gedebage is planned to be constructed in a new development refion in the south of Bandung called Summarecon Bandung, or Summarecon Teknopolis.initiated by Summarecon Bandung itself, this concert hall is dedicated to pop music and is built to be the representation of Indonesian pop music. These drawings will be used as basis to mke an optimal design. Any changes that are made in result of design processes must consider the function of each object. In construction management, these aspects include tower crane foundation design, dewatering design for excavated area, excavation design, heavy equipment lifting design. Tower crane foundations have 60 cm of diameter and 31 m depth. Driven pile foundation system is designed by determining the axial-load carrying capacity of a single driven pile based on Reese and Wright method, determining the lateral-load carrying capacity using ENSOFT LPILE software, determining the axial load carrying capacity using ENSOFT GROUP software, designing reinforcement on pile cap, designing pile head treatment, dan designing hammer type. Dewatering design for excavated area is designed using rational method because the area is less than 10 ha. Triangle section is used as drainage channel to simplify the construction process. Tsurumi KTVE 33.7 Automatic Submersible Pump is used for dewatering which has 350 litre/minute flow rate capacity and 22 m head capacity. Slope stability and the capacity of diaphragm wall must be considered for excavation design. Finite slope analysis (ordinary method of slices) is used for limited excavation area. Accessories and the load of heavy equipment need to be considered for lifting process. IHI CCH 1500 and komatsu PC 70-8 is used for excavating and lifting design.